ANALISIS DAMPAK DELAY YANG TERJADI PADA RUNWAY, APRON DAN RUANG UDARA TERHADAP OPERASIONAL PESAWAT (STUDI KASUS: BANDARA INTERNASIONAL JUANDA) - Laila Fatchiyah; Ervina Ahyudanari (Journal of Civil Engineering, 2017)
The Air transport demand still increasing continuously both of number passengers, cargo and aircraft movementswill have a direct impact on the capacity of the airport. Juanda International Airport has one runway that serves about 35-40aircraft per hour. The number of aircraft movements cause the problem of delay and wasting fuel. Delay can reduced theproductivity airport services and airlines. This goal of this paper is to analyze the airport capacity, delay and effect of delay onthe aircraft's fuel consumption. Calculations using simulation software arena with arrivals and departure modelling. The resultsshowed that in the calculation of the existing runway capacity as much as 44 scheduled aircraft movements during peak hoursthere are only 33 aircraft for 1 hour with an average delay of 29 minutes. Simulations using the software arena, delay for arrivalvaried between 0.6 minutes to 4.2 minutes and delay for departure varied between 0.8 minutes to 19 minutes. Aircraft fuelconsumption A320 for the queue 1 to 4 of aircraft varied between 67.56 lb to 270.26 lb. While fuel consumption B737-500 forthe queue 1 to 4 of aircraft varied between 131.31 lb to 525.26 lb.